Computer simulation of low-energy high-current electron beam dynamics in a long plasma-filled diode - Agafonov, A.V.; Tarakanov, V.P. (Вопросы атомной науки и техники, 2008)
Results of computer simulation of low-energy high-current electron beam dynamics in a low-impedance system
consisting of a diode with a long plasma anode, just siding with an explosive emission cathode and an auxiliary
thermionic cathode are presented. Plasma anode plays simultaneously a role of the transport channel providing
charge neutralization of high-current beam and is created by means of the residual gas ionisation by low-current,
low-voltage electron beam emitted from the auxiliary cathode in an external longitudinal magnetic field. The main
peculiarities of the beam-plasma system are discussed: 1) the formation of the beam of currents exceeding the
limiting Alven’s ones; 2) the formation of paramagnetic states of the beam under condition of beam charge density
close to the plasma density. These peculiarities complicate beam-plasma interaction significantly due to sharp nonuniform
distribution of the beam current density, significant transverse motion of the beam electrons and
redistribution of ion plasma density under the influence of high-current electron beam fields. Computer simulation
was performed using electromagnetic PIC code KARAT. Наведено результати чисельного моделювання динаміки низькоенергетичних потужнострумових електронних
пучків у низькоімпедансній плазмовій системі, що складається з діоду з довгим плазмовим анодом, що впритул прилягає
до вибухоемісійного катоду, і допоміжного термокатоду. Плазмовий анод одночасно відіграє роль каналу для
транспортування пучку і створюється за допомогою іонізації залишкового газу слабкострумовим низьковольтним
пучком від термокатоду в зовнішнім поздовжнім магнітному полі. Розглянуто основні особливості подібної пучково-
плазмової системи: 1) формування пучків зі струмами, що перевершують граничний струм Альфвена; 2) формування
парамагнітних станів пучків в умовах, коли щільність заряду пучка порівнянна із щільністю плазми. Робота виконана за
підтримкою РФФД по гранту 05-02-16442. Приведены результаты численного моделирования динамики низкоэнергетичных сильноточных электронных пучков
в низкоимпедансной плазменной системе, состоящей из диода с длинным плазменным анодом, вплотную прилегающим
к взрывоэмиссионному катоду, и вспомогательного термокатода. Плазменный анод одновременно играет роль канала
для транспортировки пучка и создается посредством ионизации остаточного газа слаботочным низковольтным пучком
от термокатода во внешнем продольном магнитном поле. Рассмотрены основные особенности подобной пучково-
плазменной системы: 1) формирование пучков с токами, превосходящими предельный ток Альфвена; 2) формирование
парамагнитных состояний пучков в условиях, когда плотность заряда пучка сравнима с плотностью плазмы. Работа
выполнена при поддержке РФФИ по гранту 05-02-16442.